DARI TRADISI KE INOVASI: UPAYA KOMUNITAS DIAJENG SEMARANG DALAM MELESTARIKAN KEBAYA DAN JARIK - Nursalima Tsalats Hadimar Putri; Siti Maziyah; Suryani, Suryani (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
As a multicultural nation, Indonesia holds an extensive and diverse cultural heritage, among which kebaya and jarik stand as profound representations of Indonesian women’s identity. Both have been officially recognized by UNESCO as elements of intangible cultural heritage. This study explores the preservation strategies of kebaya and jarik in Semarang City implemented by the Diajeng Semarang Community amidst the ongoing dynamics of modernization. Utilizing a qualitative approach with an ethnographic method, this research involved ten informants selected through purposive sampling, including community members and relevant stakeholders. The findings indicate that the Diajeng Semarang Community plays a pivotal role in sustaining the existence of kebaya and jarik through a range of creative initiatives such as social media campaigns, educational workshops, and collaborations with local designers, educational institutions, and government agencies. The study further demonstrates that the Diajeng Semarang Community has effectively positioned kebaya and jarik as cultural symbols that remain relevant within contemporary society. These findings underscore the dual function of cultural communities, not only as preservers of tradition but also as agents of social and cultural transformation. Consequently, the Diajeng Semarang Community serves as a concrete model of sustainable cultural preservation that bridges traditional values and modern practices.